Characterization of Silver Nanoparticles Internalized by Arabidopsis Plants Using Single Particle ICP-MS Analysis - Bao, Dongping; Oh, Zhen Guo; Chen, Zhong (Frontiers in Plant Science, 2016)
Despite the continual improvement of quality of life with nanotechnological applications, nanoparticles (NPs) will inevitably reach our living environment and various ecosystems. Plants act as a crucial interface between humans and their environment. The wide use of NPs has raised great concerns about the risk of potential toxicity in crop health and food safety, leading to an emerging research theme about the interaction between plants and NPs. However, even the basic issue concerning the eventual fate and characteristics of NPs after internalization is not clearly delineated due to lack of a well-established technique for NP analysis in plant tissues. With the aid of enzymatic digestion, single particle-inductively coupled plasma-mass spectrometry (SP-ICP-MS) is employed to determine the size distribution of silver nanoparticles (Ag NPs) in tissues of the model plant Arabidopsis thaliana after exposure to 10 nm Ag NPs. Our results show that Macerozyme R-10 is an appropriate enzyme to release Ag NPs from Arabidopsis plants without changing the properties of nanomaterials. The characteristics of Ag NPs obtained by SP-ICP-MS in both roots and shoots are in agreement with our transmission electron micrographs, demonstrating that SP-ICP-MS coupled with enzymatic digestion procedure is a powerful technique for quantitative determination of NPs in plant tissues. Our data reveal that Ag NPs tend to accumulate predominantly at root tissues whereby a minor portion is transported to shoot tissues. Furthermore, the measured size distribution of Ag NPs in plant tissue is centred at around 20.70 nm, larger than the average 12.84 nm in diameter, strongly implying that many internalized Ag NPs do not exist as intact individual particles but are aggregated and/or biotransformed by plant cells.